Beyond Dialogue: Etika Dialog Emmanuel Levinas - Lemanto, Eduardus (Universitas Katolik Parahyangan, 2021)
Beyond Dialogue is a subtheme of Levinas’ work of alterity & transcendence. It is his philosophical deliberation and reflection on the Judea-Christian discord. In his philosophy of dialogue Levinas takes a deep look at the core points of Seelisberg Conference of 1947 – International Emergency Conference on Anti-Semitism. He reflects on why dialogue has not ceased the contention between the Jews and the Christians. Through this article I am going to elucidate Levina’s philosophical notions of dialogue. There are two principal questions I put on the table of discourse: Why does Levinas emphasize the principle of ‘beyond dialogue’ in his notion of philosophy of dialogue? What is the ‘ethical foundation’ of dialogue in the face of conflicts of identity? This article aims to examine Levinas’ ideas of philosophy of dialogue, and also to invite the readers to draw out the insights relevant in comprehending as well as in responding to social conflicts in nowdays that Levinas contributes through his philosophical reflection.